Terapia física para mejorar las actividades de la vida diaria del adulto mayor en el hogar de ancianos Daniel Álvarez Sánchez de la ciudad de Loja, período marzo- julio 2015 - Sarmiento Mendoza, Marjorie Patricia (2015)
The present thesis entitled: PHYSICAL THERAPY TO IMPROVE THE DAILY LIFE ACTIVITIES OF ELDERLY PEOPLE IN “ DANIEL ALVAREZ SANCHEZ ” NURSING HOME FROM THE LOJA CITY, PERIOD MARCH-JULY 2015. This study is framed within the type of action research, through the intervention, the type of study is descriptive, correlational and explanatory, the methods fall into three areas: theoretical-diagnostic, design and planning of the alternative, and evaluation and assessing the effectiveness of the alternative, using the methods: scientific, synthetic, analytical, inductive, deductive, descriptive, historical, dialectical and hermeneutical, applying an observation as technique which allowed to analyze the research topic; besides as the instrument was used the Rating Scale of Daily Life Activities of Barthel Index, the center has a population of 50 elderly people, as the criterion of the sample is not random the scale allowed to select the sample which was of 31 adults. With the results obtained it was determined that the proposal helped in a high percentage thus concluding that the physical therapy workshop applied to elderly people benefited to perform the daily life activities, recommending to professionals to continue implementing the activity proposed